Intermittent and mild persistent asthma: how therapy has changed - Di Cicco, Maria Elisa; Leone, Maddalena; Scavone, Maria; Miraglia Del Giudice, Michele; Licari, Amelia; Duse, Marzia; Brambilla, Ilaria; Ciprandi, Giorgio; Caffarelli, Carlo; Tosca, Mariangela (Acta Biomedica Atenei Parmensis, 2021)
In the last few years much attention has been focused on research on severe asthma and the role of biologicals in its treatment, also in children. However, mild asthma is way more common in childhood and still causes as many as 30-40% of asthma exacerbations requiring emergency consultation. The management of “intermittent” and “mild persistent” asthma phenotypes is still a matter of debate, even if the role of inhaled corticosteroids, both continuous and intermittent, is a cornerstone in this field. Nevertheless, updates on the strategies to manage these patients are coming, since evidence emerged on the role of inflammation also in these asthma phenotypes as well as on the potential side effect and risks of short-acting beta 2 agonists overuse, which is common in patients for which they have been prescribed as the only as-needed treatment. Unsurprisingly, international guidelines, including GINA, are starting to recommend associating a corticosteroid when using a reliver. In this paper we overview the (r)evolution regarding the management of intermittent and mild persistent asthma. We also focus on the importance of knowing the chemical and physical characteristics of drugs and inhaler devices in order to optimize the treatment and reach the distal airways, as well as of trying to achieve a good compliance to treatments, especially in adolescents, for which it is currently possible to rely also on new digital health technologies.